Association between adaptive behaviour and age in adults with Down syndrome without dementia: examining the range and severity of adaptive behaviour problems. (20th November 2014) - Makary, A. T.; Testa, R.; Tonge, B. J.; Einfeld, S. L.; Mohr, C.; Gray, K. M.
Abstract Background Studies on adaptive behaviour and ageing in adults with Down syndrome (DS) (without dementia) have typically analysed age‐related change in terms of the total item scores on questionnaires. This research extends the literature by investigating whether the age‐related changes in adaptive abilities could be differentially attributed to changes in the number or severity (intensity) of behavioural questionnaire items endorsed. Methods The Adaptive Behaviour Assessment System‐II Adult (ABAS‐II Adult) was completed by parents and caregivers of 53 adults with DS aged between 16 and 56 years. Twenty adults with DS and their parents/caregivers were a part of a longitudinal study, which provided two time points of data. In addition 33 adults with DS and their parents/caregivers from a cross‐sectional study were included. Random effects regression analyses were used to examine the patterns in item scores associated with ageing. Results Increasing age was found to be significantly associated with lower adaptive behaviour abilities for all the adaptive behaviour composite scores, expect for the practical composite. These associations were entirely related to fewer ABAS‐II Adult items being selected as present for the older participants, as opposed to the scores being attributable to lower item severity. Conclusions This study provides evidence for a differential pattern of age‐related change for various adaptive behaviour skills in terms of range, but not severity. Possible reasons for this pattern will be discussed. Overall, these findings suggest that adults with DS may benefit from additional support in terms of their social and conceptual abilities as they age.